Non-Genomic Actions of Estrogens on the DNA Repair Pathways Are Associated With Chemotherapy Resistance in Breast Cancer - Jiménez-Salazar, Javier E.; Damian-Ferrara, Rebeca; Arteaga, Marcela; Batina, Nikola; Damián-Matsumura, Pablo (Frontiers in Oncology, 2021)
Estrogens have been implicated in the etiology of breast cancer for a long time. It has been stated that long-term exposure to estrogens is associated with a higher incidence of breast cancer, since estradiol (E2) stimulates breast cell growth; however, its effect on DNA damage/repair is only starting to be investigated. Recent studies have documented that estrogens are able to modify the DNA damage response (DDR) and DNA repair mechanisms. On the other hand, it has been proposed that DDR machinery can be altered by estrogen signaling pathways, that can be related to cancer progression and chemoresistance. We have demonstrated that E2 promotes c-Src activation and breast cancer cell motility, through a non-genomic pathway. This review discusses scientific evidence supporting this non-genomic mechanism where estrogen modifies the DNA repair pathways, and its relationship to potential causes of chemoresistance.